Organizational culture at Texas community colleges and the leadership response to the enrollment management environment - Watts, Tracee Tollett (Kansas State University, 2024)
Community colleges have experienced many challenges since their establishment in 1902; however, the 21st century has brought new obstacles and opportunities. In turn, community college leaders have been called upon to address challenges such as the COVID-19 global pandemic, the demand from students for virtual course offerings, and financial concerns. Declining birth rates and questions about the value of college have exacerbated enrollment concerns (Kelderman, 2019). With the changing enrollment management environment, higher education professionals acknowledge the need to adapt organizational culture and leadership strategies to address the challenges. This adaptation requires prioritizing student success through retention, persistence, graduation, certificate completion, or transfer while highlighting the institution’s strengths and value to attract more students and increase enrollment. This study used an explanatory sequential design mixed-methods study to collectively form a comprehensive understanding of how executive leaders and enrollment management personnel assessed organizational culture in Texas community colleges and how executive leaders responded to the changing enrollment management environment. The theoretical framework guiding this study was Schein’s (1986) organizational culture theory. Quinn and Rohrbaugh’s (1983) Competing Values Framework (CVF) was the conceptual framework guiding this study. Using Cameron and Quinn’s (n.d.) Competing Values Culture Assessment (CVCA), the results of this study show there are differences in the assessment of organizational culture between executive leaders and enrollment management personnel. Furthermore, the results illustrate that executive leaders and enrollment management personnel encountered internal and external challenges, which have had positive and negative effects on enrollment at their institutions. These challenges created unique opportunities to reconsider traditional approaches and reimagine strategies to fulfill the foundational mission of community colleges and meet the expectations and desires of students, employees, and the broader community.
Keywords: Enrollment management; Organizational culture; Texas community colleges; Competing Values Culture Assessment; Organizational culture theory; Competing Values Framework